Relationship of Smartphone usage, Disclosure and Interpersonal closeness among undergraduate students: none - Arif, Sara; Maryam Munir; Dr. Saima Majeed (University of Wah Journal of Social Sciences, 2024)
The purpose of the study was to explore the relationship between smartphone usage, disclosure and interpersonal closeness among undergraduates in Lahore Pakistan. . A cross-sectional correlational design was used to examine the relationship between study variables. A convenience sampling was employed on sample of 350 male and female university students. The subscale of the Functional Idiographic Assessment Template-Questionnaire; disclosure and interpersonal closeness (FIAT-Q; D) and problematic mobile phone usage scale (PUMP) were used to collect data. It was hypothesized that smartphone usage has a negative impact on students’ interpersonal closeness. Pearson correlation analysis was used to determine the relationship between the study variables. Gender differences in Smartphone usage and interpersonal closeness were assessed through an independent sample t-test. The findings revealed a positive correlation between Problematic phone usage and interpersonal closeness of undergraduate students. Keywords: Smartphone usage, interpersonal closeness, undergraduate students